2016
DOI: 10.1093/hmg/ddw092
|View full text |Cite
|
Sign up to set email alerts
|

GWAS meta-analysis of 16 852 women identifies new susceptibility locus for endometrial cancer

Abstract: Endometrial cancer is the most common gynecological malignancy in the developed world. Although there is evidence of genetic predisposition to the disease, most of the genetic risk remains unexplained. We present the meta-analysis results of four genome-wide association studies (4907 cases and 11 945 controls total) in women of European ancestry. We describe one new locus reaching genome-wide significance (P < 5 × 10 ) at 6p22.3 (rs1740828; P = 2.29 × 10, OR = 1.20), providing evidence of an additional region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…In the largest GWAS meta-analysis assessing endometrial cancer risk, we discovered nine new genetic risk regions. We also confirmed the association of genetic variants with endometrial cancer risk at seven of the eight previously published genetic risk regions for this disease 5 8 . Using this larger GWAS-meta dataset, we were also able to confirm the previously published Mendelian randomization studies finding that higher BMI is causal for endometrial cancer risk 20 , and the protective effect of later age of menarche on endometrial cancer risk 19 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the largest GWAS meta-analysis assessing endometrial cancer risk, we discovered nine new genetic risk regions. We also confirmed the association of genetic variants with endometrial cancer risk at seven of the eight previously published genetic risk regions for this disease 5 8 . Using this larger GWAS-meta dataset, we were also able to confirm the previously published Mendelian randomization studies finding that higher BMI is causal for endometrial cancer risk 20 , and the protective effect of later age of menarche on endometrial cancer risk 19 .…”
Section: Discussionsupporting
confidence: 85%
“…Risk of endometrial cancer is approximately double for women who have a first degree relative with endometrial cancer 2 , 3 . Rare high-risk pathogenic variants in mismatch-repair genes, PTEN , and DNA polymerase genes 4 explain a small proportion of endometrial cancers, and the eight previously published common endometrial cancer-associated single-nucleotide polymorphisms (SNPs) identified by genome-wide association studies (GWAS) studies 5 8 together explain <5% of the familial relative risk (FRR).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these reports support the hypothesis that pathogenic germline variants in the exonuclease proofreading domains of POLE (exons [9][10][11][12][13][14] and POLD1 (exons 8-13) that are deleterious to polymerase proofreading function predispose to endometrial cancer. To date, three likely pathogenic POLD1 variants (c.947A4G (p.Asp316Gly); c.1433G4A (p.Ser478Asn); c.1421 T4C (p.Leu474-Pro)) have been identified in nine women with endometrial cancer (proven or obligate carriers) from four families, and two likely pathogenic POLE variants (c.1421 T4C (p.Leu424Val); c.1089C4A (p.Asn363Lys)) in three endometrial cancer patients from two families.…”
Section: Pold1 (And Pole)supporting
confidence: 72%
“…To date, several common single-nucleotide polymorphisms (SNPs) have been shown to be convincingly associated with endometrial cancer risk from largescale candidate locus analysis and genome-wide association analyses. These include 'low-risk' SNPs at/near HNF1B, 8,9 the TERT-CLPTM1L cancer risk region, 10 the CYP19A1 locus encoding the aromatase enzyme pivotal to estrogen biosynthesis, 11 ESR1 encoding the estrogen receptor, 12 SH2B3, 13 SOX4, 14 and also KLF5, AKT1, EIF2AK4, HEY2/NCOA7, and at the MYC multicancer locus. 15 Consistent with findings for most other cancers, the endometrial cancer risks associated with these common variants are considered modest (odds ratios ranging from 0.84 to 1.27).…”
mentioning
confidence: 99%
“…Three SNPs have been identified in or around KLF5 that are associated with endometrial cancer. The G allele of rs11841589 (OR 1.15, 95% CI 1.11 to 1.21; p=4.83×10 -11 ), the A allele of rs9600103 (OR 1.23, 95% CI 1.16 to 1.30; p=3.76×10 -12 ) and C allele of rs7981863 (OR 1.16, 95% CI 1.12 to 1.20; p=2.70×10 -17 ) have all been found to be associated with an increased likelihood of endometrial cancer in large European cohorts 21 30 34. It is worth noting that these SNPs are not independent, and hence they quite possibly tag the same causal variant.…”
Section: Resultsmentioning
confidence: 99%